INVESTIGATION OF MECHANICAL PROPERTIES OF AL2O3-20 WT % ZRO2 COMPOSITES AS A FUNCTION OF SINTERING TEMPERATURE - Hossen, M. Moazzam; Chowdhury, F. U. Z.; Gafur, M. A.; Abdul Hakim, A.K.M.; Nasrin, S. (European Scientific Journal, ESJ, 2014)
High purity nanocrystalline α-alumina powder was mixed with 20 wt% ZrO2 by slurry method sintered at temperature (Ts) 1450°C, 1500°C, 1550°C and 1600°C for 2 hour. The density, porosity, structural properties and mechanical properties of Al2O3-ZrO2 composites with respect to sintering temperature have been explored in the present work. The XRD spectra indicate that α-Al2O3, t and m-ZrO2 are the crystalline phases present in 20 wt% ZTA composites for all sintering temperature. It is observed that with higher sintering temperature the intensity of m-ZrO2 phases increases and the t-ZrO2 phases decreases. However, t-ZrO2 retention becomes much easier to trigger the transformation to monoclinic. Higher density of 20 wt% ZTA has been achieved at 1600ºC, whereas the highest porosity was obtained for sintering temperature 1450°C.The microstructures of the samples was studied by using SEM which represents highly homogeneous and finer structure at 1600ºC. The effect of sintering temperature on hardness, elastic modulus and flexural strength were investigated and has been found to increase with the increase of sintering temperature. Maximum hardness, elastic modulus and flexural strength were achieved for the Al2O3– 20 wt% ZrO2 composites sintered at 1600°C.